EloPSO: energy aware elephant swarm optimization for mobile adhoc networks - Khan , Burhan ul Islam; Olanrewaju, Rashidah Funke; Ali, Nor'ashikin; Shah , Asadullah (penseejournal.com, 2014)
The high pace increase in wireless mobile communication based applications have made mobile Adhoc Network (MANET)an essential communication paradigm to ensure Quality of Service (QoS) provisioning. MANET characterizes itself with its decentralized network establishment nature and architectural dynamicity.The predominant QoS parameters in MANETs are end-to-end delay, network throughput, overheads, network life time and others. The mobility and the lack of optimum resource sharing mechanism cause the QoS degradation in MANETs. This lifespan of any node deployed in Adhoc network is in proportion with the associated level of components and functions. Data drop and successive data regression also cause the exhaustion on energy conservation, in this paper a hybrid cross layer MAC optimization scheme has been developed for MANETs real time applications. Specifically an optimization approach based on Elephant swarm behaviour named ElePSO has been projected to optimize the node life time and throughput. Asa CSMA/CA protocol is not effective for multhop data transmission, thus the Ele PSO scheme has been incorporated with TDMA-MAC to ensure energy aware communication. Simulation results show that the ElePSO out perform other bio-inspired optimization techniques like ( Particle Swarm Optimization) PSO and (Ant Colony Optimization) ACO. Results confirm that ElePSO exhibits higher active node while bearing lower communication overhead as compared to PSO and ACO.